(untitled) (Third Sector Social Economic Review, 2025)
Although the Republic of Turkey, immediately following its foundation, established numerous institutions aligned with its republican principles and enacted corresponding legislation, it also continued to employ certain long-standing Ottoman administrative structures and their associated legal frameworks. Foundations (vakıflar) are among these enduring institutions. During the Ottoman era, many functions that fell within the remit of local administrations were in fact carried out by the judiciary (kadılık), guilds (loncalar), and foundations. As in the Ottoman period, the Directorate General of Foundations (Vakıflar Genel Müdürlüğü), established to bring all foundations under a single umbrella, now operates under the Ministry of Culture and Tourism. The subject of this study is the management and usage of the immovables in the General Directorate of Foundations in the context of the transformation of the foundation institution from the Ottoman Empire to the present day. In this study, it is aimed to evaluate the potential of foundation immovables to contribute to local public services and to examine the practices of the use of these immovables within the framework of central-local administration relations. While the fact that such a study has not been done before, which reveals the immovable inventory and usage of the General Directorate of Foundations, it is very important in terms of understanding the methods of evaluation of foundation immovables and evaluating the practices.